Comprehensive conservative treatment for multiple metastases of skull osteosarcoma: A case report - Jiang, Dawei; Wang, Jingming; Chen, Qian; Wu, Junyi; Xu, Ming; Yu, Xiuchun (Frontiers in Neurology, 2023)
Background: Skull osteosarcoma is relatively rare, and it is difficult to diagnose by medical history and imaging examination due to the complex structure and diverse components of the brain. Consequently, here is a rare number of patients who can undergo neoadjuvant chemotherapy before operation. Although neoadjuvant chemotherapy plays an important role in the treatment of osteosarcoma, there is still a "bottleneck" in the current treatment of osteosarcoma. When pulmonary metastasis occurred, or surgical treatment cannot be Enneking appropriate, the choice of treatment will become a difficult problem. Case: A 16-year-old male patient with multiple metastases of skull osteosarcoma was reported. The patient underwent skull tumor resection at another hospital in November 2018, during which process the biopsy revealed epithelioid osteoblastoma-like osteosarcoma. After 33 months, the patient found pulmonary metastases and multiple bone metastases. Then the patient underwent multiple conservative treatments which include Denosumab, Anlotinib and DIA chemotherapy at our hospital. After a series of 6 cycles of treatment, the patient can walk without aid. Lactate dehydrogenase (LDH) and Alkaline phosphatase (AKP) decreased to normal. Fluorodeoxyglucose (FDG) metabolism in all bone metastases decreased to normal except in the proximal left femur, and the FDG metabolism in the left femur is significantly lower than that before treatment. Multiple bone metastases showed different extent high-density calcification, and the volume of the local bone metastases has been reduced significantly. Conclusion: We found that multiple conservative treatments, which include Denosumab, Anlotinib and DIA chemotherapy, can improve patients’ life quality, and help avoid further osteolytic destruction for patients with skull osteosarcoma and multiple metastases. Its specific mechanism and scope of the application still need to be further studied.